#TITLE_ALTERNATIVE# - KURNIAWAN (NIM 20506015), CEPI
Semiconductor energy gap and the amenity to be modified in semiconductor materials with perovskite structure are ones of the reason why these materials are actively studied. Studies on the photoluminescence properties of rare earth doped (Ca,Sr)TiO3 prepared by sonochemical method have been carried out were become one of the reason of the usage of this material on the research (Ca,Sr)TiO3 further will be written as CSTO:RE, where RE = Pr3+, Eu3+, and Tb3+. During synthesis, ultrasonic irradiation was exposed on precursor with stochiometric ratio of (Ca,Sr) and Ti in ethanol: water (1:1) solvent for 2 hours. The obtained products then were heated at various temperatures of 100 degrees C, 500 degrees C, 800 degrees C and 1000 degrees C for 2 hours. The white powder obtained after heated has crystallite size of 18-58 nm. The sample then characterized with XRD powder, SEM, and spectrofluorometer. The SEM images showed that the CSTO:Pr grain were in spherical form and become homogenous at the highest temperatures. The peaks that indicated perovskite structure can be observed on the X-ray diffraction pattern after heating at above 500 oC. The impurities are also observed and identified as TiO2 and CaO. The X-ray diffraction pattern of CaxSr1-xTiO3, indicated that with the increasing of x, 2θ shifts towards larger ones caused by substitution of cation Sr2+ that larger than Ca2+ (rSr2+>rCa2+). Meanwhile, the refinement of X-ray diffraction pattern using La Bail method encountered that for CSTO:RE has conformity (Rp and Rwp < 8 %) with space group Bmmb (Z=8). Photoluminescence spectrum of CSTO:RE excited with λ = 220 nm shows a similar patterns of each other, that is the appearances of peak at 3,4 and 2,4 eV. The spectrum at this green color area estimated come from electronic transition in CSTO. Whereas spectrum characteristically to CSTO:Pr emerges peak at 2,06 eV after its excited using λ = 325 nm. This band emerges from electronic transition 1D2-3H4. The CSTO:Eu excited using 463 nm have two emission peaks at 2,02 eV (transition 5D0-7F2) and 2,09 eV (transition 5D0-7F1). Meanwhile, the same spectrum from CSTO:Tb was not observed. We could argue that its luminescence color is in the same region with the host material of CSTO (green color). This was supported by the fact that there is an enhancement of photoluminescence peak at 3,4 eV.